Is the robotic revolution stunting surgical skills? - Damien J. Lazar, MD MBA; George S. Ferzli, MD FACS (Surgery Open Science, 2024)
This perspective piece aims to examine the impact of the growing utilization of robotic platforms in general and minimally invasive surgery on surgical trainee experience, skill level, and comfort in performing general surgical and minimally invasive procedures following completion of training. We review current literature and explore the application of robotic surgery to surgical training, where minimum case thresholds and breadth distribution are well defined, and where development of surgical technique is historically gained through delicate tissue handling with haptic feedback rather than relying on visual feedback alone. We call for careful consideration as to how best to incorporate robotics in surgical training in order to embrace technological advances without endangering the surgical proficiency of the surgeons of tomorrow. Key message: The large-scale incorporation of robotics into general and minimally invasive surgical training is something that most, if not all, trainees must grapple with in today's world, and the proportion of robotics is increasing. This shift may significantly negatively affect trainees in terms of surgical skill upon completion of training and must be approached with an appropriate degree of concern and thoughtfulness so as to protect the surgeons of tomorrow.